The determination of antifeedant effect of Neem Azal T/S on almond leaf bee Cimbex quadrimaculata (Müller, 1766) (Hymenoptera: Cimbicidae) larvae - Özgen, İnanç; Güral, Yunus; Koç, İbrahim; Topdemır, Aykut (My University, 2025)
In this study, the antifeeding index (AFI) value of Neem Azal T/S plant extract against the larvae of the almond leaf bee Cimbex quadrimaculata Müller, 1766 (Hymenoptera: Cimbicidae) was determined under laboratory conditions. The leaf dipping method was employed, and the measurement concentrations were set at 0% (control), 0.8%, 1.0%, 1.2%, 2%, 4%, 6%, 8%, and 10%. The extract was applied to the 3rd and 4th larval period of the pest. The antifeeding indexes of different doses of the extract were calculated using both choice and non-choice methods, and the differences between the data were assessed using the Kruskal-Wallis test. The differences between the choice and non-choice methods were also statistically determined using the Mann-Whitney U test. As a result of the study, the highest AFI value in both larval stages was recorded for the 10% concentration in both choice and no-choice methods. The lowest AFI value was observed at the lowest concentration of 0.8% in both methods during the 4th larval stage of the pest. It was found that as the concentration of extract increased, the C. quadrimaculata larvae consumed fewer leaves. In conclusion, it was determined that the highest AFI values occurred at the of 8% and 10%, indicating that the effectiveness of Neem Azal T/S increased with increasing dosage.
Keywords: Efficacy; Cimbex quadrimaculata; Larvae; Neem Azal T/S; Maximum Antifeeding Index (AFI)